The visual communication of the local religiosity as a part of the Bulgarian Cultural Heritage (Research Announcements "Heritage BG", 2025)
The creation of visual works dedicated to local religiosity as part of the Bulgarian cultural heritage forms is an interdisciplinary approach to anthropological research, because in addition to the visual presentation of names, facts, dates and events allow the audience to immerse themselves in the modern era. This is successfully applied in the acquisition of knowledge, skills and competencies in various fields, as well as acquaintance with local religiosity. The main components of the impact are multichannel, mass, speed of distribution and perception. In this way, two vector lines are traced: the first – the visualization of the Bulgarian cultural and historical space and the second – the connection of these concepts with linguodidactic aspects as a model of research. References:Halachev 2009: Halachev, Lubomir. Documentalnoto kino. Stupka po stupka. Sofia.Jordanova 2014: Jordanova, Kremena. Ezhednevieto v selo Slaveino - sreshta na dve identichnosti. In: Vayra smesena. Aspekti na vsekidnevieto v dve rodopski sela, Sofia, 11-36.Kanevski 2018: Kanevski, Konstantin. Tchudotvornoto aqzmo i paraklisite v Momchilovtzi. Smolian.Kaftandjiev 1996: Kaftandjiev, Hristo. Vizualna comunikacia. Sofia.Koleva 2012: Koleva, Irina. Etnopsihologicheski model na obrazovatelno vzaimodeistvie. Sofia.Kotzeva 2014: Kotzeva, Violeta. Praznici, pamet, identichnost. Oshte edin opit varhu tolerantnostta (po primera na selo Slaveino, obshtina Smolayn). In: Vayra smesena. Aspekti na vsekidnevieto v dve rodopski sela, Sofia, 56-72.Spasov 2012: Spasov, Radoslav. Suzdavane na dokumentalni filmi za rusenskite curkvi ‘Sveta Troitsa’ i ‘Sveti Velicomuchenik Georgi’. In: Almanah za istoriyata na Ruse, Vol. XII, 236-244.Spasov 2015: Spasov, Radoslav. Vizualni aspecti na istoriyata. Sofia.Spasov 2018: Spasov, Radoslav. Vizualna comunicacia i moderni metodi za populqrizirane na Sveti Dimitriji Basarbovski i skalnia manastir krai Basarbovo, Rusensko. In: CAMERA DANUBIANA – obrazi ot gradovete v stranite po Dunav. Izvestia na RIM-Ruse, Vol. ХХ, 106-116.Stoeva 2005: Stoeva, Emilia. Viziata v dokumentalnoto kino. Sofia.Tepavitcharov 2014: Tepavitcharov, Veselin. Tolerantnostta i doverieto – kluch kum integraciata na etnicheskite i religioznite obshnosti v Bulgarskoto obshtestvo (primerut na selata Slaveino i Vievo, obshtina Smolqn). In: Vayra smesena. Aspekti na vsekidnevieto v dve rodopski sela, Sofia, 73-87.
Keywords: Christianity; anthropological space; media